2011
DOI: 10.1056/nejmoa1011376
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Dialysis Catheter Malfunction with Recombinant Tissue Plasminogen Activator

Abstract: The use of rt-PA instead of heparin once weekly, as compared with the use of heparin three times a week, as a locking solution for central venous catheters significantly reduced the incidence of catheter malfunction and bacteremia. (Current Controlled Trials number, ISRCTN35253449.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
123
2
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(131 citation statements)
references
References 36 publications
(31 reference statements)
2
123
2
4
Order By: Relevance
“…The risk for adverse events was similar (70% and 68.7%) in the rt-PA and heparin groups, respectively with no statistically significant difference in the serious adverse events between the two groups (20.9 % and 29.6%). Also, patients in the rt-PA group did not have a higher frequency and severity of bleeding episodes [5].…”
mentioning
confidence: 83%
See 3 more Smart Citations
“…The risk for adverse events was similar (70% and 68.7%) in the rt-PA and heparin groups, respectively with no statistically significant difference in the serious adverse events between the two groups (20.9 % and 29.6%). Also, patients in the rt-PA group did not have a higher frequency and severity of bleeding episodes [5].…”
mentioning
confidence: 83%
“…Locking with heparin however, does not prevent bacterial colonization and subsequent development of CRBSI. Moreover, in vitro studies have shown that heparin may induce biofilm formation [4].Replacing heparin with recombinant tissue plasminogen activator (rt-PA) once a week, as a dialysis catheter locking solution significantly reduced the incidence of catheter malfunction and CRBSI in a well conducted multicenter, double-blind, randomized controlled trial from Canada by Hemmelgarn and colleagues [5]. The authors were able to decrease the rates of catheter malfunction by 50% and…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Thrombolytic locking solution has also shown promise in reducing bacteremias. The use of recombinant tissue plasminogen activator (rt-PA) substituting heparin at the midweek dialysis session significantly reduced the incidence of catheter malfunction and bacteremia [25] . When used for prevention, ALS significantly lowers CLABSI risk.…”
Section: Antimicrobial Lock Solutionsmentioning
confidence: 99%